HUBUNGAN NILAI HEMATOKRIT DAN NILAI JUMLAH TROMBOSIT PADA PASIEN DEMAM BERDARAH DENGUE - Hukom, Andrew O. E.; Warouw, Sarah M.; Memah, Maya; Mongan, Arthur E. (eBiomedik, 2013)
Abstract: Dengue hemorrhagic fever (DHF) has been a global problem especially for children. There are two main pathophysiological changes occur in DHF. The first one is an increased vascular permeability and the second one is the disorder of haemostasis. Haematocrit and thrombocyte count are laboratory parameters that are needed for monitoring the development of DHF. This was a retrospective analytical study with a cross sectional design. Samples were patients who were diagnosed as dengue hemorrhagic fever in RSUP Prof. Dr. R.D. Kandou Manado in 2012. Inclusion criteria were patients aged <15 years, were diagnosed based on WHO 1997, and were already tested for haematocrit test and platelet count. Data obtained from the medical records were analyzed by using t test and Spearman?s correlation test. There were 137 children with DHF in 2012, and as samples we used 62 children. The t-test of haematocrit values showed a P-value 0.0001 which meant that there was a significant increase of haematocrit among DHF patients. The t-test of thrombocyte counts showed a P-value 0.0001, which meant that there was a significant decrease of thrombocyte count among the DHF patients. The Spearman test showed a correlation of haematocrit level and thrombocyte counts among DHF patients with a P-value 0.133. Conclusion: There was no significant correlation between haematocrit and thrombocyte count among dengue hemorrhagic fever patients.Keywords: dengue hemorrhagic fever, children, haematocrit, thrombocyte coountAbstrak: Demam berdarah dengue (DBD) telah menjadi masalah masyarakat internasional terutama pada anak-anak. Dua perubahan patologik utama pada penyakit DBD yaitu peningkatan permeabilitas kapiler dan gangguan hemostasis. Hematokrit dan hitung trombosit merupakan parameter laboratorik yang diperlukan untuk memantau perkembangan DBD. Penelitian ini bersifat analitik retrospektif dengan desain potong lintang. Sampel penelitian ialah pasien anak yang terdiagnosis DBD di RSUP Prof. Dr. R. D. Kandou Manado selama periode tahun 2012. Kriteria inklusi ialah pasien berusia <15 tahun dan telah terdiagnosis menurut kriteria WHO 1997, serta melakukan pemeriksaan laboratorium hematokrit dan trombosit. Penelitian ini menggunakan catatan rekam medik, dan untuk analisis statistik digunakan uji t dan Spearman?s correlation test. Dari 137 anak dengan DBD pada periode 2012, diambil 62 anak sebagai sampel. Melalui uji t untuk hematokrit didapatkan nilai P = 0,0001 yang menunjukkan terdapat peningkatan bermakna nilai hematokrit pada pasien DBD. Melalui uji untuk jumlah trombosit didapatkan nilai P = 0,0001, yang menunjukkan terdapat penurunan bermakna nilai jumlah trombosit pada pasien DBD. Hasil uji Spearman terhadap korelasi nilai hematokrit dan nilai jumlah trombosit memperlihatkan nilai P = 0,133 (? ? = 0,05). Simpulan: Tidak terdapat hubungan bermakna antara nilai hematokrit dan nilai jumlah trombosit pada pasien demam berdarah.Kata kunci: demam berdarah dengue,anak, hematokrit, trombosit